2003
DOI: 10.1162/089892903321107819
|View full text |Cite
|
Sign up to set email alerts
|

Parietal Representation of Symbolic and Nonsymbolic Magnitude

Abstract: The close behavioral parallels between the processing of quantitative information conveyed by symbolic and nonsymbolic stimuli led to the hypothesis that there exists a common cerebral representation of quantity (Dehaene, Dehaene-Lambertz, & Cohen, 1998). The neural basis underlying the encoding of number magnitude has been localized to regions in and around the intraparietal sulcus (IPS) by brain-imaging studies. However, it has never been demonstrated that these same regions are also involved in the quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
276
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 371 publications
(316 citation statements)
references
References 25 publications
25
276
2
1
Order By: Relevance
“…In our study, we selected our ROIs based on these studies (Hyde & Spelke, 2009; Libertus et al., 2007) and found the symbolic integration effect in these ROIs. Given that these posterior sites are spatially close to parietal cortex and the fact that parietal cortex, especially the IPS, has been implicated in numerical processing in other studies (Ansari et al., 2005; Fias et al., 2003; Piazza et al., 2004), it is tempting to link our findings to the function of parietal cortex. Yet, the spatial resolution of the EEG/ERP method constrains the power to make such inferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we selected our ROIs based on these studies (Hyde & Spelke, 2009; Libertus et al., 2007) and found the symbolic integration effect in these ROIs. Given that these posterior sites are spatially close to parietal cortex and the fact that parietal cortex, especially the IPS, has been implicated in numerical processing in other studies (Ansari et al., 2005; Fias et al., 2003; Piazza et al., 2004), it is tempting to link our findings to the function of parietal cortex. Yet, the spatial resolution of the EEG/ERP method constrains the power to make such inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies using different paradigms confirmed this finding (Hsu & Szücs, 2012; Hyde & Spelke, 2009; Rubinsten, Dana, Lavro, & Berger, 2013). In fMRI studies, the IPS was repeatedly found to be activated in nonsymbolic and symbolic number comparison tasks (Ansari, Garcia, Lucas, Hamon, & Dhital, 2005; Fias, Lammertyn, Reynvoet, Dupont, & Orban, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…He found that reaction times tend to rise when the discrimination becomes finer (see Welford, 1960). Since then, the distance effect has been shown many times using pairs of lines (e.g., Johnson, 1939;Fias et al, 2003). However, there are numerous examples of other stimuli that show a distance and/or size effect (Table 1).…”
Section: Similar Effect Patterns With Different Kinds Of Quantity: Thmentioning
confidence: 99%
“…For example, Fias et al (2003) obtained a size effect when subjects compared pairs of angles or pairs of lines. When grouping reaction times (RTs) on the basis of the size of the smallest angle (or line) in the pair, participants responded significantly slower with increasing size (or length).…”
Section: Similar Effect Patterns With Different Kinds Of Quantity: Thmentioning
confidence: 99%
See 1 more Smart Citation